Heritabilities and genetic correlations of ultrasound-measured ribeye area with other performance traits in Brangus cattle - Johnson, M.Z.; Schalles, R.R.; Olson, W.; Dikeman, Michael E. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Heritabilities and genetic correlations for ultrasound-measured ribeye area and fat thickness, as well as growth traits and scrotal circumference, were determined using performance records of 1613 Brangus calves born from 1987 to 1990. Moderate heritabilities of .39 for weaning and .40 for yearling ultrasound- measured ribeye area indicate that selection to change these traits should be effective. The positive, and generally large, genetic correlations between ultrasound-measured ribeye areas and growth traits indicate that genetic change of these traits can be made in tandem. The low heritability (.14) of fat thickness, the small amount of fat, and the lack of variation would make it very difficult to change the genetic ability of animals to deposit fat.
Keywords: Beef; Heritability; Genetic correlation; Ultrasound-measured traits; Growth; Scrotal circumference; Brangus cattle